2005
DOI: 10.1002/cncr.21565
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic juice cytology in the diagnosis of intraductal papillary mucinous neoplasm of the pancreas

Abstract: BACKGROUND The examination of pancreatic juice cytology could hypothetically contribute to the establishment of a definite diagnosis of malignant intraductal papillary mucinous neoplasm of the pancreas (IPMN), but to the authors' knowledge, its significance has not been confirmed to date. The current study was conducted to assess the diagnostic value of pancreatic juice cytology in IPMN and to examine the usefulness of peroral pancreatoscopy (POPS) in sampling pancreatic juice. METHODS The study subjects were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 26 publications
(39 reference statements)
2
57
0
1
Order By: Relevance
“…Branch duct IPMNs that could be followed up were selected, and also cytologic examination of pancreatic juice was performed for all the IPMNs during ERCP in order to exclude malignant neoplasms. Cytology is useful for discriminating benign from malignant branch duct IPMNs, although this modality is not as useful as it is for discriminating benign from malignant main duct IPMNs ( [22] and our unpublished data).…”
Section: Discussionmentioning
confidence: 90%
“…Branch duct IPMNs that could be followed up were selected, and also cytologic examination of pancreatic juice was performed for all the IPMNs during ERCP in order to exclude malignant neoplasms. Cytology is useful for discriminating benign from malignant branch duct IPMNs, although this modality is not as useful as it is for discriminating benign from malignant main duct IPMNs ( [22] and our unpublished data).…”
Section: Discussionmentioning
confidence: 90%
“…A study by Yamaguchi et al [37] reported an improved ability to diagnose IPMNs by pancreatic cytology using "mother-baby" systems. Importantly, this study also found that there is no diagnostic value for pancreatic juice cytology in the diagnosis of pancreatic carcinoma.…”
Section: Diagnostic Applicationsmentioning
confidence: 99%
“…Most of the studies on pancreatoscopy have been conducted in patients with intraductal papillary mucinous neoplasms (IPMNs) [36][37][38][39]. Diagnostic yield of POPS with or without POPS-guided biopsy for malignancy in IPMN are reported, and range from 50 to 68% sensitivity and from 87 to 100% specificity.…”
Section: Extent Of Intrapapillary Mucinous Neoplasmsmentioning
confidence: 99%